Decentralisation of Collective Bargaining in Germany - Recent Trends and Challenges - Thomas Haipeter; Sophie Rosenbohm (Universität Duisburg-Essen, Institut Arbeit und Qualifikation (IAQ), 2023)
Decentralisation of collective bargaining takes place in different forms: wild decentralisation and organised decentralisation. Organised decentralisation takes two forms: derogations and through the transfer of regulatory competences to the workplace level entailing a shift in responsibilities from the collective bargaining arena to works councils and codetermination. The relevance of these forms differs significantly between sectors in Germany as shown by the examples of the metalworking industry and the retail sector. Wild decentralisation poses a fundamental threat to the German system of collective bargaining. Organised decentralisation demands for a new and more active division of work between trade unions and works councils.
urn:nbn:de:hbz:465-20230424-080207-3
Keywords: 300